Association between polymorphism at codon 469 of the ICAM-1 gene and Henoch-Schönlein purpura in an Iranian cohort - Salehi, Shima; Hozhabrpour, Amir; Takrim Nojehdeh, Somayeh; Mojbafan, Marzieh (Nucleosides, nucleotides & nucleic acids, 2025)
Henoch-Schönlein purpura (HSP) is a common form of IgA1-mediated blood vessel inflammation affecting mainly children. Intercellular adhesion molecule-1 (ICAM-1) gene polymorphisms have been shown to be associated with HSP in different populations; in this study, we investigated its potential association and influence on the development of severe complications in Iranian HSP patients. Twenty-three patients diagnosed with IgAV/HSP according to the criteria of the American College of Rheumatology (ACR) with 53 age- and sex-matched control subjects were referred to us. Cases and controls were genotyped using Sanger sequencing. Based on our research data, we found an association between codon 469 K/E of the ICAM1 gene and risk of HSP. Our results revealed that KK genotype and allele K are more common in control than in the HSP group, therefore the subjects with KK genotype are protected against HSP. Our data also suggested that the genotype EE is associated with higher risk of HSP progression compared to KK genotype.